You are on page 1of 2

) (

f ]_ [ -a, b F f ]_ [ -a, b

f a b :

) a f ( x )dx = F ( x )a = F ( b ) - F ( a
:

a
a f ( x )dx = 0
b
b
kf
x
dx
=
k
(
)
a
a f ( x )dx
:

a
b
f
x
dx
=
(
)
b
a f ( x )dx
b
b
b
f
x
+
g
x
dx
=
f
x
dx
+

(
)
(
)
(
)

a
a
a g ( x )dx

) (k

b
c
b
f
x
dx
=
f
x
dx
+
(
)
(
)
a
a
c f ( x )dx

:
f ( x ) 0 :
b
a f ( x )dx 0 :

] "x [ a, b
f ( x ) g ( x ) :
b
b
f
x
dx

(
)
a
a g ( x )dx :

] "x [ a, b

f ][a,b

b
1
] [ a,b f ( x )dx :

b-a a

:
f g ] [ -a, b g ' f' g

] [ -a, b

a f '( x ) g ( x ) dx = f ( x ) g ( x )a - a f ( x ) g '( x )dx


b

rr
o,i, j

u . A :

r r
o i j
r

1.u . A = i j

20

f ][a;b

Cf
:
x = a y = b:

g ][a;b

Cf
Cg
x = a : y = b:

a f ( x ) dx .u.A

f
x
g
x
dx
(
)
(
)
a
.u.A

f
][a,b

a f ( x )dx .u.A

f
][a,b

a -f ( x )dx .u.A

f
][a,c
f
][c, b

) ( Cf ) ( Cg

][a,b

) ( Cf ) ( Cg

][a,c
) ( Cg ) ( Cf
][c, b
:

( Cf

][a,b
:

b

V = p ( f ( x ) ) dx u.v
a

21

b
c

a f ( x )dx + c -f ( x )dx .u.A

a ( f ( x ) - g ( x ) )dx .u.A

b
c

a ( f ( x ) - g ( x ) )dx + c ( g ( x ) - f ( x ) )dx .u.A